Yoghurt : science and technology - Tamime, A. Y.; Robinson, R. K. (Richard Kenneth) (Boca Raton, FL : CRC Press ; Cambridge, England : Woodhead Pub., 1999)
The new edition includes a discussion of 'bio-yoghurts' with their important implication for manufacturing practice. Contents include: Background to manufacturing practice; Processing plant and equipment; Cleaning and hygiene; Traditional and new developments in yoghurt production; Microbiology of yoghurt and 'bio' started cultures; Biochemistry of fermentation; Preservation and production of starter cultures; Nutrition; Quality control and HACCP.
Preliminaries; Contents; Preface to second edition; Preface to first edition; 1 Historical background; 2 Background to manufacturing practice; 3 Processing plants and equipment; 4 Plant cleaning hygiene and effluent treatment; 5 Traditional and recent developments in yoghurt production and related products; 6 Microbiology of yoghurt and bio starter cultures; 7 Biochemistry of fermentation; 8 Preservation and production of starter cultures; 9 Nutritional value of yoghurt; 10 Quality control in yoghurt manufacture.
Includes bibliographical references.
Keywords: Yogurt